Cerebral angiography using transauricular access in a rabbit model: a new technique. (January 2021) - Kim, Hak Jin; Choi, Seon Hee; Kim, So-Hyeon; Kim, Yong-Woo; Jhun, Byung Hak; Lee, Deug-Woo; Yoo, Jin-Wook
Background: Cerebral angiography in a rabbit model is widely used in the field of interventional radiology. Conventionally, the femoral artery is used for cerebral angiography in radiology departments. However, angiographic studies require surgical cutdown of the femoral artery, which is technically difficult. Purpose: To evaluate a new cerebral angiography technique involving a transauricular approach in a rabbit model. Material and Methods: In each of 10 rabbits, central auricular arteries were punctured in the right or left ear with a 20-gauge i.v. catheter. A microcatheter (2.0 F) with a 0.016-inch guide wire was introduced through the i.v. catheter and advanced to the aortic arch. The microcatheter and guide wire were advanced selectively into cerebral arteries and angiography was performed. Results: Central auricular arteries were successfully punctured with 20-gauge i.v. catheters. After approaching the aortic arch, microcatheter tips and guide wires were advanced manually to cerebral arteries on both sides. Difficulties in selecting the carotid arteries were resolved by using a looping technique within the cardiac chamber. Microcatheter loops within the cardiac chamber disappeared or remained during artery superselection. Conclusion: Transauricular cerebral angiography appears to be a feasible technique for brain or carotid intervention studies in rabbits. In addition, vertebral angiography using a transauricular approach is possible using the looping technique. Selection of carotid or vertebral arteries on each side was not difficult when the microcatheter and guide wire were looped within the cardiac chamber. The ear chosen for the initial puncture does not appear to be important.